2018
DOI: 10.1007/s00383-018-4335-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux in children with neurological impairment: a systematic review and meta-analysis

Abstract: Neurologically impaired children (NIC) suffer severe gastroesophageal reflux (GER) with poor fundoplication outcome. Aims of the study were: (1) to determine the recurrence of GER after fundoplication in NIC; (2) to compare fundoplication versus gastro-jejunal tube feeding insertion (GJ) and fundoplication versus total esophagogastric dissociation (TEGD) in primarily treating GER in NIC. Using defined search strategy, two investigators identified all comparative studies reporting the mentioned procedures to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…Compared to the available literature [7,12,13], our study tried to shed a light on a controversial topic: the advantage of an ARP to reduce respiratory impairment in the neuropathic child needing gastrostomy. Gastrostomy itself is a contributing factor in the decision for fundoplication in many centers; although open gastrostomy has been demonstrated to promote reflux [14], the minimally invasive techniques have been shown to not exacerbate reflux quantitatively or qualitatively in most children [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the available literature [7,12,13], our study tried to shed a light on a controversial topic: the advantage of an ARP to reduce respiratory impairment in the neuropathic child needing gastrostomy. Gastrostomy itself is a contributing factor in the decision for fundoplication in many centers; although open gastrostomy has been demonstrated to promote reflux [14], the minimally invasive techniques have been shown to not exacerbate reflux quantitatively or qualitatively in most children [15].…”
Section: Discussionmentioning
confidence: 99%
“…In this population, nutrition and primary aspiration risks are often tackled with non-oral methods of food delivery, such as naso-gastric tube (NGT) or gastrostomy/gastrojejunostomy (GJ) placement [4], with the latter two being sometimes associated with an anti-reflux procedure (ARP) or even total esophago-gastric dissociation (TOGD) [5,6]. In NI children failure of ARP is reported high as 50% [7]. Although nutritional management is a crucial aspect for these patients, there is no univocal consensus on the approach to be applied [4]: this is mainly due to either lack of measured objective outcomes or to the reduced number of patients enrolled in each report.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of discharge data for 342 pediatric patients, found no difference in hospital admissions for aspiration pneumonia, other pneumonia or respiratory distress before or after anti-reflux surgery ( 100 ). Finally, a meta-analysis by Lauriti et al showed that gastro-jejunal feeding was no better at preventing respiratory complications than anti-reflux surgery in children with NI ( 101 ). Large prospective, high quality trials would be useful to determine if and when treatment of GOR is useful in improving respiratory morbidity.…”
Section: Respiratory Dysfunctionmentioning
confidence: 99%
“…It is reasonable to counsel families that symptoms typically improve after 1 year of age in the overwhelming majority of healthy infants. GERD does, however, demonstrate an increased prevalence in children affected by: prematurity, obesity, neurological impairment, congenital heart disease, congenital diaphragmatic hernia, gastrointestinal (GI) tract abnormalities, and chromosomal abnormalities (2,(14)(15)(16)(17)(18)(19)(20)(21). Refractory GERD refers to GERD symptoms that do not respond to medical treatment after 8 weeks (10).…”
Section: Epidemiology Pathogenesis and Presentationmentioning
confidence: 99%